MEDIA IPA INTERAKTIF BERBASIS LECTORA INSPIRE UNTUK MENINGKATKAN KETERAMPILAN ANALISIS - Agnesi Sekarsari Putri; Jumadi Jumadi (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2021)
Natural science material is abstract such as the solar system causing students to have difficulty understanding the material so visualization is needed to study it. Interactive learning media is needed so that abstract material becomes simpler and easier to understand, learning is interesting, and meaningful. The purpose of this study was to determine the effect of Lectora Inspire-based interactive science media on students' analytical skills. The type of research used is a quasi-experimental with pretest posttest nonequivalent control group design. The population used consisted of 6 classes with cluster random sampling sampling technique taken 2 classes, namely VII B as the experimental class and class VII E as the control class, each of which amounted to 30 students. The results of the analysis using the Independent Sample T-Test show that there is an influence of interactive science media based on Lectora inspire to improve students' analytical skills. Therefore, the use of interactive science media based on Lectora inspire can be used in learning to improve students' analytical skills.